Cutaneous Application of Celecoxib for Inflammatory and Cancer Diseases - Quiñones, Oliesia G.; Pierre, Maria B. R. (Current Cancer Drug Targets, 2019)
Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) and particularly selective cyclooxygenase-2 (COX-2) inhibitors such as celecoxib (Cxb) are considered promising cancer chemopreventive for colon, breast, prostate, lung, and skin cancers. However, the clinical application to the prevention is limited by concerns about safety, potential to serious toxicity (mainly for healthy individuals), efficacy and optimal treatment regimen. Cxb exhibits advantages as potent antiinflammatory and gastrointestinal tolerance compared with conventional NSAID's. Recent researches suggest that dermatological formulations of Cxb are more suitable than oral administration in the treatment of cutaneous disease, including skin cancer. To date, optimism has been growing regarding the exploration of the topical application of Cxb (in the prevention of skin cancers and treatment of cutaneous inflammation) or transdermal route reducing risks of systemic side effects. Objective: This paper briefly summarizes our current knowledge of the development of the cutaneous formulations or delivery systems for Cxb as anti-inflammatory drug (for topical or transdermal application) as well its chemopreventive properties focused on skin cancer. Conclusion: New perspectives emerge from the growing knowledge, bringing innovative techniques combining the action of Cxb with other substances or agents which act in a different way, but complementary, increasing the efficacy and minimizing toxicity.
Keywords: skin inflammation